HEALTH EDUCATION THROUGH MEDIA LEAFLETS ON THE FREQUENCY OF POST-MENOPAUSAL FEMALE SEXUAL RELATIONS - Somantri, Iwan; Hartono, D; Februanti, S (International Journal of Psychosocial Rehabilitation, 2020)
As women age, physical and psychological changes will occur, especially in the menopause period. Physical and psychological changes in postmenopausal women can make sexual intercourse sick and make you uncomfortable and reduce sex drive. The purpose of this study was to determine the effect of health education through leaflet media on the frequency of sexual relations in postmenopausal women in Tasikmalaya. The research design uses a method quasi-experiment, with one group approaches pretest and the post-test group without a control group. Sampling with consecutive sampling technique, as many as 30 respondents. Data analysis used univariate and bivariate analyzes using the paired t-test. The results showed no effect of health education through the media leaflets on the frequency of post-menopausal female sexual relations, p-value 0.491 (p> 0.05). Health education through leaflets does not affect the frequency of postmenopausal female sexual relations. It is recommended for nurses to provide alternative nursing actions to postmenopausal women so that they can increase the frequency of sexual relations and can improve the quality of life of postmenopausal women.